Socialization of Lifestyle in Accordance with Health Protocols for Visitors to Medan City Market Center and Giving Masks, Multivitamins, Hand Sanitizers - Sembiring, Asan Petrus; Situmorang, Nasib Mangoloi; Marbun, Doaris Ingrid; Adriansyah; Riszki (Talenta Publisher, 2023)
A worldwide spread of coronavirus that started in the Chinese city of Wuhan is known to cause disease in humans. Several types Corona are known to cause respiratory tract infections in humans ranging from fever, cough and cold to more serious ones such as shortness of breath to death. Its transmission spreads so quickly throughout the world that it is called a pandemic. The addition of the number of Covid-19 cases is still happening and there are no visible signs of ending due to the implementation of health protocols that are not carried out by the community as a whole. In an effort to suppress the transmission of COVID-19 in the community, we provide education/counseling to sellers and visitors at the Medan Market Center who are vulnerable to transmission and the occurrence clusters of COVID-19, as well as providing free health protocol facility assistance in the form of masks, hand sanitizers and multivitamins. This is done to educate the public so that there is a change in lifestyle behavior in an effort to prevent the emergence of clusters. This activity was carried out by visiting visitors and traders at the Medan Market Center on September 14, 2021. Visitors and traders at the Medan Market Center began to understand the lifestyle according to health protocols and were willing to play a role in implementing joint health protocols in preventing the transmission of Covid-19.